Volatile Constituents of the Flowers and Leaves-Stems of Three Doronicum taxa from Turkey - Akpinar, Kurtulus; Yildirim, Nuri; Cuncu, Osman; Yayli, Nuran; Terzioglu, Salih; Yayli, Nurettin (Asian Journal of Chemistry, 2010)
The composition of the essential oils obtained from fresh flowers and leaves-stems of 3 Doronicum taxa, 2 of them are endemic to Turkey, have been studied. The essential oils were separately obtained from hydrodistillation in a clevenger-type apparatus and their analyses were performed by GC and GC-MS. A range of 14-27 compounds were identified, constituting over 89.3 to 97.7 % of total oil composition. Sesquiterpene hydrocarbons were shown to be the main group of constituents of all 3 Doronicum taxa. The main component of the flowers and leaves-stems in the essential oils of Doronicum orientale and Doronicum bithynicum ssp. sparsipilosum was (E)-β-farnesene (41.1, 35.7, 47.5 and 55.4 %, respectively); while (E)-caryophyllene (24.2 and 52.7 %) was the major compound in the essential oils of Doronicum macrolepis.